STAT3/LINC00671 axis regulates papillary thyroid tumor growth and metastasis via LDHA-mediated glycolysis - Nan Huo; Rui Cong; Zhi-jia Sun; Wen-chao Li; Xiang Zhu; Chun-yuan Xue; Zhao Chen; Lu-yuan Ma; Zhong Chu; Yu-chen Han; Xiao-feng Kang; Song-hao Jia; et al. (Cell Death and Disease, 2021)
Abstract Lactate dehydrogenase A (LDHA), a critical component of the glycolytic pathway, relates to the development of various cancers, including thyroid cancer. However, the regulatory mechanism of LDHA inhibition and the physiological significance of the LDHA inhibitors in papillary thyroid cancer (PTC) are unknown. Long non-coding RNA (lncRNA) plays a vital role in tumor growth and progression. Here, we identified a novel lncRNA LINC00671 negatively correlated with LDHA, downregulating LDHA expression and predicting good clinical outcome in thyroid cancer. Moreover, hypoxia inhibits LINC00671 expression and activates LDHA expression largely through transcriptional factor STAT3. STAT3/LINC00671/LDHA axis regulates thyroid cancer glycolysis, growth, and lung metastasis both in vitro and in vivo. In thyroid cancer patients, LINC00671 expression is negatively correlated with LDHA and STAT3 expression. Our work established STAT3/LINC00671/LDHA as a critical axis to regulate PTC growth and progression. Inhibition of LDHA or STAT3 or supplement of LINC00671 could be potential therapeutic strategies in thyroid cancer.